2020
DOI: 10.21203/rs.3.rs-25306/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dental Faculty’s Knowledge and Attitude regarding COVID-19 disease in Qassim, Saudi Arabia

Abstract: Background: Present study aimed to explore the knowledge and attitude of dental faculty at Qassim University, regarding novel COVID 19 disease. Methods: The cross-sectional survey was conducted on the faculty at undergraduate dental school. The self-designed e-survey was administered to 78 faculty members to assess their knowledge and attitudes towards the COVID-19 disease. Data analysis was conducted by using SPSS version 23. Descriptive statistics were reported as frequency and percentages. Chi-square test w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 20 publications
1
13
1
2
Order By: Relevance
“…In accordance with a study conducted in Uganda (Olum et al 2020), this study reported that females manifested lower knowledge levels compared to males. Our results are inconsistent with prior studies which reported that females had a signi cantly higher score than males (Al-Hazmi et al 2018;Zhong et al 2020; and one study which reported no signi cant correlation of gender and specialty with both knowledge and attitude (MQ et al 2020).…”
Section: Discussioncontrasting
confidence: 99%
“…In accordance with a study conducted in Uganda (Olum et al 2020), this study reported that females manifested lower knowledge levels compared to males. Our results are inconsistent with prior studies which reported that females had a signi cantly higher score than males (Al-Hazmi et al 2018;Zhong et al 2020; and one study which reported no signi cant correlation of gender and specialty with both knowledge and attitude (MQ et al 2020).…”
Section: Discussioncontrasting
confidence: 99%
“…This finding is consistent with two earlier studies. 21,22 Intentions toward positive COVID-19 IPC behavior was also significantly associated with the age, current position, and work affiliation of the DHCWs. The older agegroup work in the academic field in both public and private sectors demonstrated greater positive intentions than the younger age-group.…”
Section: Discussionmentioning
confidence: 94%
“…25,29 Hence, the Saudi government's understanding of the disease and preparedness may have played a pivotal role in the prevention of disease transmission. Similarly, previous KSA-based studies of DHCWs, 19 dental faculty 20 and HCWs 27 have also praised the efforts and role of the Saudi Arabian government in timely dissemination of information. Contrary to the present findings, some studies indicate that more COVID-19-related information is obtained from physician websites or social media.…”
Section: Dhcps' Knowledge About Covid-19mentioning
confidence: 99%
“…The use of PPE, including N95 or FFP2/FFP3 masks, gloves, gowns, protective glasses, visors and headgear caps, is of the utmost importance during any dental procedures. 20,43 DHCPs demonstrated good practice management regarding clinical procedures. They agreed that during the COVID-19 pandemic, rubber dams, four-handed dentistry and saliva ejectors should be used along with minimal aerosol-producing procedures.…”
Section: Covid-19mentioning
confidence: 99%
See 1 more Smart Citation